COLOUR STABILITY OF STEAMED BLACK LOCUST, BEECH AND SPRUCE TIMBERS DURING SHORT-TERM PHOTODEGRADATION - Varga Dénes (WOOD RESEARCH, 2021)
Black locust (Robinia pseudoacacia L.), beech red heartwood (Fagus sylvatica L.) and spruce (Picea abies Karst.) wood samples were treated in saturated steam at 100, 110 and 120 degrees C then irradiated using a UV emitter mercury lamp in order to test their colour stability. Colour change was evaluated and presented in the CIE Lab colour coordinate system. Untreated black locust, beech and spruce specimens as control samples were irradiated using the same mercury lamp. Results revealed that beech produced the greatest colour stability during both steam treatment and the following UV treatment while spruce was the most sensitive species to photodegradation. Steaming reduced the colour change intensity only for black locust during photodegradation. Both redness and yellowness change demonstrate this colour stability increase. Steaming at 120 degrees C resulted in the greatest protection against the colour alteration of black locust caused by photodegradation. The investigated thermal treatments did not change the photodegradation properties of beech and spruce specimens. A considerable increase in colour saturation of the specimens was generated by steaming, and the saturation value further increased during the UV treatment.